International Relations Theory and the "Social Whole": Encounters and Gaps Between IR and Sociology. Issue 2 (10th June 2013) - Albert, Mathias; Buzan, Barry
<x xml:space="preserve">Abstract</x> This article explores some basic issues which arise from International Relations (IR) theory also being a form of social theory in a broader sense. Many of these issues are related to the question of a "social whole, " that is, whether international relations/International Relations is one of many parts of a social whole, on what grounds it is differentiated from other parts, and whether it operates on a distinct level of social reality. We argue that these questions have been addressed in many forms of IR theory, but mostly only implicitly, and that the failure to make explicit assumptions about a social whole is probably due to the relative neglect of the subject in modern Sociology. The article argues that implicit assumptions about a social whole can be unearthed by looking at the concepts of systems, levels, and sectors, discussing debates about each of these in turn. Openly addressing IR theory as social theory, and spelling out images of a social whole, allows one to gain a sharper understanding of some of the basic analytical categories used, and to judge whether they form plausible delimitations of social reality within a wider social context.